Contribution of English Teachers in Improving Religiousness Students at Islamic Boarding Schools - Yusuf, Safwa N.; Yusuf , Aisyiyah Mumtazah N.; Ibrahim, Fathum (Labor Program Studi Pendidikan Sosiologi, 2024)
The extent of the quality and capacity of a teacher determines success in education. A good teacher can become a subject teacher, but also a teacher who can educate his students until they achieve objective education, that is, giving students intellectual skills at a time embedding religious, ethical, and national values. This writing means to see English language education teachers' contribution to increasing religious students' knowledge and attitudes at the Boarding school Biharul Ulum. Study This nature discriminates empiricist who sees contributions from the cognitive and affective realms. Research results find that English education teachers Can make significant contributions in adding knowledge and attitudes to religious students. The cognitive contribution was made by entering religious materials in English lessons and stage discussion entitled religious use. Whereas contribution is effectively done by embedding spiritual and social values through communication and guidance in the use of English as a language of familiarity. This teacher's contribution shows that if two eyes lessons or more can be integrated into the frame, it will increase knowledge and religious attitudes.